Comprehensive all-sky search for periodic gravitational waves in the sixth science run LIGO data - Abbott, B. P.; Davies, G. S.; LIGO Scientific Collaboration and Virgo Collaboration (American Physical Society, 2016)
We report on a comprehensive all-sky search for periodic gravitational waves in the frequency band 100–1500 Hz and with a frequency time derivative in the range of [−1.18,+1.00]×10−8  Hz/s. Such a signal could be produced by a nearby spinning and slightly nonaxisymmetric isolated neutron star in our galaxy. This search uses the data from the initial LIGO sixth science run and covers a larger parameter space with respect to any past search. A Loosely Coherent detection pipeline was applied to follow up weak outliers in both Gaussian (95% recovery rate) and non-Gaussian (75% recovery rate) bands. No gravitational wave signals were observed, and upper limits were placed on their strength. Our smallest upper limit on worst-case (linearly polarized) strain amplitude h0 is 9.7×10−25 near 169 Hz, while at the high end of our frequency range we achieve a worst-case upper limit of 5.5×10−24. Both cases refer to all sky locations and entire range of frequency derivative values.
© 2016 American Physical Society. This is the publisher Version of Record Manuscript. Please refer to any applicable publisher terms of use.